Two cases of colonic tumors observed by linked color imaging and texture and color enhancement imaging with the tablet‐image comparison method. Issue 1 (24th August 2021) - Tomita, Yuri; Yoshida, Naohisa; Inoue, Ken; Hashimoto, Hikaru; Sugino, Satoshi; Hirose, Ryohei; Dohi, Osamu; Itoh, Yoshito
Abstract: An endoscope system using 5‐color light‐emitting diodes (LEDs) (EVIS X1: CV‐1500, Olympus Co., Tokyo, Japan) was released worldwide in July 2020. In addition to the improvement of narrow band imaging (NBI), this system enables texture and color enhancement imaging (TXI). TXI makes the lesion reddish and supports better visibility of colorectal lesions in comparison to white light imaging for improving lesion detection. On the other hand, another 4‐color LED endoscope system (ELUXEO: BL‐7000; Fujifilm, Tokyo, Japan) has been on the market in the West since 2017. This system enables blue light imaging (BLI) and linked color imaging (LCI). Generally, the accurate comparison between two images obtained by two different endoscope systems is difficult. To resolve this problem, we developed a method named the tablet‐image comparison (TIC) method. TIC is a simple, easy, and paperless method to get images under similar conditions of two endoscope systems for an accurate comparison. We herein report two colorectal lesions in which accurate comparisons of images between TXI and LCI and between improved NBI and BLI obtained in the EVIS X1 and ELUXEO systems were performed using the TIC method. One was IIa 30 mm (high‐grade dysplasia) and the other was IIa 25 mm (low‐grade adenoma). A detailed comparison between TXI and LCI could be performed by TIC. In these two cases, with a distant view, TXI showed greater redness than LCI. LCI showed slightly higher brightness than TXI. In magnified TXI and LCI, the irregularities observed were similar to NBI and BLI, respectively.